Pengembangan Potensi Pelaku UMKM di Pasar Gede Malang Untuk Mengekspor Produknya ke Luar Negeri - Akmal, Ali Musa Tawakal-Ul; Imaningsih, Niniek (Peneliti.net, 2023)
National Income is an indicator of economic growth related to whether or not the economy is progressing in a country. The components that make up national income are the level of consumption, the level of investment, the level of government spending and also the level of import and export. In its application, MSME actors as providers of goods and the public as consumers of goods have contributed to the high and low levels of national income. Information and the government's role in facilitating export activities create the potential for MSME players to trade their products to foreign markets more easily, so this also increases the possibility that MSME actors' reach to consumers will be wider. The purpose of writing this journal is to find out the potential development of SMEs in Pasar Gede Malang to exporting their products to foreign markets.